Boron effects on nodule development in pea plants cultivated in lowland soils - de Azevedo, Watson Rogério; Faquin, Valdemar; Moreira, Fátima Maria de Souza; Júnior, Antônio Claret de Oliveira; Lisboa, Carolina Cardoso (Pesquisa Agropecuaria Brasileira, 2002)
The objective of this work was to evaluate the effect of boron on nodule development in pea Pisum sativum L. plants cultivated in lowland soils under greenhouse conditions from May to July, 1998. Samples of Alluvial Soil, Low Humic Gley, Humic Gley and artificially drained Bog Soil were collected from a layer 0-20 cm deep. The samples were previously cultivated with radish plants that received lime, P, K, S, Cu and Zn and doses of B (0, 0.25, 0.5, 1.5, 3.0 and 6.0 mg dm-3). Before pea cultivation only K was applied (100 mg dm-3). The experimental design was totally randomized in a factorial scheme 4x6 with three replicates. Seeds were inoculated with Rhizobium leguminosarum strains (BR 618 and BR 619). To verify native strains, three pots of each soil were cultivated without inoculated seeds with same lime and fertilizers doses and 0.5 mg dm-3 of boron. After 45 days, the experiment was harvested. Native strains were not found in the evaluated soils. Boron affected nodule development and nitrogenase activity in the pea plants in Low Humic Gley and artificially drained Bog Soil.